Hamlet in Russia between the second half of the nineteenth century and the first two decades of the 20th century - Tagliagambe, Silvano (Scenari, 2021)
The definition of chirality, from the Greek cheir meaning “hand”, is due to Lord Kelvin who enunciated it during the “Baltimore Lectures”, a series of lectures held at Johns Hopkins University in Baltimore, starting from October 1st 1884, and published twenty years later, in 1904, in which the English scientist, among other things, stated: “I call any geometrical figure, or groups of points, chiral, and say it has chirality, if its image in a plane mirror, ideally realized, cannot be brought to coincide with itself“. Chirality is, therefore, the geometric property of a group of points or atoms in space, or of a solid object, of not being superimposable on its mirror image. These structures, defined as chiral, have the peculiar property of being devoid of symmetry elements of the second kind, namely, a mirror plane, an center of inversion, or a rotation-reflection. The environment is rich in chiral objects: our hands are the example par excellence, but there are many others, from the shell of a snail to a spiral galaxy. The paper analyzes the use of chirality and mirror images in famous representation of Shakesperare’s Hamlet at the Moscow Art Theater (1911) with the direction of Konstantin Stanislavkij and the sets by Edward Gordon Craig. In line with a tendency within the Symbolist movement to view Shakespeare’s play as a work of poetry rather than as one for the stage, Craig conceived of the production as a symbolis monodram in which every aspect of production would be subjugated to the play’s protagonist: the play would present a dream-like vision as seen through Hamlet’s eyes. To support this interpretation, Craig wanted to have Hamlet present on-stage during every scene, silently observing those in which he did not participate. The kernel of Craig’s monodramatic interpretation lay in the staging of the first court scene. The stage was divided sharply into two areas through the use of lighting: the background was brightly lit, while the foreground was dark and shadowy; the screens were lined up along the back wall and bathed in diffuse yellow light. From a high throne upon which Claudius and Gertrude sat, which was bathed in a diagonal, bright golden beam, a pyramid descended, representing the feudal hierarchye; the pyramid gave the illusion of a single, unified golden mass, from which the courtier’s heads appeared to stick out through slits in the material. In the foreground in dark shadow, Hamlet lay slouched, as if dreaming. A thin gauze was hung between Hamlet and the court, further emphasising the division. On Claudius’ exitline the figures remained in place while the gauze was loosened, so that the entire court appeared to melt away before the audience’s eyes, as if they had been a mirror image, a projection of Hamlet’s thoughts that now had turned elsewhere. Craig’s theatrical staging of Hamlet, rich of references to chirality, is very topical and interesting, as it seems to effectively describe an atmosphere that we can define as “hamletic”.